Metal-Organic Frameworks Facilitate Nucleic Acids for Multimode Synergistic Therapy of Breast Cancer - Qian, Yue (Langmuir : the ACS journal of surfaces and colloids, 2023)
Compared with traditional medical methods, gene therapy and photodynamic therapy are the new fields of cancer treatment, and they more accurately and effectively obtain preferable therapeutic effects. In this study, a chemotherapy drug-free nanotherapeutic system based on ZIF-90 encapsulated with Ce6-G3139 and Ce6-DNAzyme for gene and photodynamic therapies was constructed. Once entering the cancer cell, the therapy system will decompose and release Zn2+, Ce6-G3139, and Ce6-DNAzyme in the acidic environment. On the one hand, G3139 binds to the antiapoptotic gene BCL-2 in tumor cells and downregulates related proteins to inhibit tumor proliferation. On the other hand, Zn2+ produced by the decomposition of ZIF-90 can be used as a cofactor to activate the cleavage activity of DNAzyme to initiate gene therapy. Proliferation and metastasis of tumors were further inhibited by DNAzyme, targeting and cutting the gene of human early growth factor-1 (EGR-1). In addition, the photosensitizer Ce6 carried by the nucleic acid will produce cytotoxic ROS to kill cancer cells after irradiation. The results of this study demonstrated that the designed nanoplatform, which synergistically combines gene and photodynamic therapies, has shown great potential for cancer treatment